Perilaku Menyimpang dalam Novel Dia adalah Dilanku 1990 Karya Pidi Baiq - Dini Putri Jaya; Zulfadhli Zulfadhli (Persona: Kajian Bahasa dan Sastra, 2022)
This study aims to describe (1) the forms of deviant behavior in the novel Dilan: he is Dilanku by Pidi Baiq, (2) the causes of deviant behavior in the novel Dilan: he is Dilanku by Pidi Baiq, and (3) the impact of deviant behavior in the novel. in the novel Dilan: he is Dilanku Tahun 1990 by Pidi Baiq. This type of research is literary research using descriptive method. The research data are in the form of words, phrases, clauses, sentences, narratives about characters, speeches about characters and actions of characters in the story in the novel Dilan: he is Dilanku Tahun 1990 by Pidi Baiq. The data collection in this study was carried out in three stages, namely reading and understanding the novel, marking things related to forms of deviant behavior, the causes of deviant behavior, the impact of deviant behavior contained in the novel Dilan: he was Dilanku Tahun 1990 by Pidi Baiq , and taking an inventory of data to obtain data related to polygamy portraits. There are four data analysis techniques in this study, including: reading the novel under study, describing the data according to the problem formulation used, interpreting the collected data, and making conclusions and the results of the description of the data format. The results of this study explain that 1) the forms of deviant behavior in the novel Dilan: he is Dilanku by Pidi Baiq are: antisocial, and violent. 2) the causes of deviant behavior in the novel Dilan: he is Dilanku by Pidi Baiq are environmental factors and feelings of disappointment, and environmental influences and the mass media. (3) the impact of deviant behavior in the novel Dilan: he is Dilanku by Pidi Baiq are: crime, and the fading of values and norms.